Jenis-Jenis Tumbuhan Talas (Araceae) di Kecamatan Rasau Jaya Kabupaten Kubu Raya - Masnur Turnip, Suci Maretni, Mukarlina (Universitas Tanjungpura, 2017)
The research on the species of araceae plants in Rasau Jaya Subdistrict of Kubu Raya Regency was conducted from December 2015 until February 2016. Sampling was done by the cruise method that explored Rasau Jaya Subdistrict which was divided into 6 stations. Station 1 was located in the village of Rasau Jaya Satu, station 2 in the village of Rasau Jaya Dua, station 3 in the village of Rasau Jaya Tiga, station 4 in the village of RasauJaya Umum, Station 5 in the village of Bintang Mas and Station 6 located in the Village of Pematang Tujuh. This research aims to identify the species of Araceae plants in Rasau Jaya Subdistrict of Kubu Raya Regency. This research obtained as many as 12 species of Araceae plants with four varieties of the Caladium bicolor which include the 11 genera namely Alocasia, Caladium, Colocasia, Cyrtosperma, Dieffenbachia, Homalomena, Lasia, Pistia, Rhapidopora, Syngonium and Xanthosoma.